ASSOCIATION BETWEEN SHORT SLEEP DURATION AND OBESITY IN MEDICAL STUDENTS - Mishra, Tapaswini; Mohapatra, Dipti; Behera, Manasi; Mishra, Srimannarayan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Adequate sleep has been considered important for the adolescent's health and well-being. On the other hand, self-imposed sleep curtailment is now recognized as a potentially important and novel risk factor for obesity. The objective of the study is to find the association between short sleep duration and obesity (by calculating the body mass index [BMI]) among medical students. Methods: The study was conducted on 100 medical students. A brief history of sleep duration was taken. The height and weight were taken and the body mass index (BMI) was calculated by formula weight in kg / height in m2. Based on the BMI criteria the students were classified into six groups: Underweight, normal, overweight, obese class I, obese class II and obese III. The waist circumference (WC) Â was also taken. Â The data obtained were statistically analysed by ANOVA test and the p < 0.5 was considered significant. Results: The present cross-sectional study showed that there is an association between short sleep duration and obesity which was highly significant (p<0.001). This study also shows that there is an association between short sleep duration and waist circumference which was also highly significant (p<0.001). Conclusion: The present study observed a high association of short sleep duration among medical students of IMS and SUM Hospital and that short sleep duration was significantly associated with increased risk of overweight and obesity. We should further investigate whether adults adopting a healthy lifestyle with short sleep duration would improve their sleeping habits or not. Keywords: Sleep duration, Body mass index, Waist circumference, Obesity.